2021
DOI: 10.1186/s12978-021-01133-8
|View full text |Cite
|
Sign up to set email alerts
|

Seeking menstrual products: a qualitative exploration of the unmet menstrual needs of individuals experiencing homelessness in New York City

Abstract: Background There has been increasing recognition that certain vulnerable populations in the United States of America struggle to meet their menstruation-related needs, including people experiencing homelessness. Media and policy attention on this subject has focused on the provision of free menstrual products to vulnerable populations, including a New York City legislative bill, which guarantees access to menstrual products for Department of Homeless Services shelter residents (Intros 1123-A). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 19 publications
1
28
1
1
Order By: Relevance
“…By specifying for product distribution in bathrooms, a recommendation from female students, the policy aims to enhance girls' agency in maintaining their menstrual privacy and reducing missed class time. Additional evidence from a study examining period product distributions for people experiencing homelessness further validates the importance of removing gatekeepers, as respondents indicated experiences of shame and humiliation when having to formally request for period products from service providers (81). Furthermore, product distribution strategies that depend on school nurses, common in the U.S.A, can be problematic.…”
Section: Discussionmentioning
confidence: 88%
“…By specifying for product distribution in bathrooms, a recommendation from female students, the policy aims to enhance girls' agency in maintaining their menstrual privacy and reducing missed class time. Additional evidence from a study examining period product distributions for people experiencing homelessness further validates the importance of removing gatekeepers, as respondents indicated experiences of shame and humiliation when having to formally request for period products from service providers (81). Furthermore, product distribution strategies that depend on school nurses, common in the U.S.A, can be problematic.…”
Section: Discussionmentioning
confidence: 88%
“…They report supplying almost six times as many products since the pandemic began [ 47 ]. While, to date, no published UK research study has documented the impact of Covid-19 on period poverty, a recent US survey observed that menstrual product insecurity was strongly predicted by pandemic related loss of income, with low income and / or low educational attainment populations at even greater risk [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…These ndings suggest great potential for period policies among other universities and in community settings. Along with champions and nancial support as highlighted by Gruer et al [14], this study highlights the importance of gaining buy-in from the larger community as well. Similar policies can be implemented in other communities to increase access and reduce stigma, speci cally by including feedback from the community.…”
Section: Discussionmentioning
confidence: 52%